The exploration of dietary adherence among haemodialysis patients in Hospital Kulim, Kedah/ Asmah Zatulnatakim, Hanee Fakhrurazzi and Mohd Ramadan Ab Hamid - Zatulnatakim, Asmah; Fakhrurazzi, Hanee; Ab Hamid, Mohd Ramadan (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Non-adherence towards dietary restriction is a common phenomenon among patients due to multifactorial causes. Knowledge, socioeconomic status, social support, together with perceived attitude and perceived behaviour, are said among the factors affecting adherence. Noncompliance to dietary restriction can lead to adverse long-term effects including deterioration of the cardiovascular system, heart failure, hypertension, and pulmonary oedema. End stage renal disease (ESRD) patients are required to follow dietary regimen about hemodialysis treatment ensuring effective treatment. The dietary regimen includes fluid, sodium, potassium and phosphate restrictions. This study aimed to explore the understanding of hemodialysis diet, barriers to adhering dietary restriction and the appropriate methods of nutrition education to the patients. An exploratory study conducted with a total of ten participants from Hospital Kulim Dialysis Center. A semi-structured interview was conducted in an average of 60 minutes to 80 minutes each participant. Hemodialysis diet knowledge was fair in every participant as everyone able to describe each restriction briefly. Most common barriers to adhere are related to human behaviour which is resistant to change, lack of control and lack of awareness in adapting dietary restriction in daily intake. Healthcare professional should focus on motivating patients to adhere to dietary restrictions by conducting individual counselling as frequent as relevant to help the patient understand and cope with dietary modifications suitable with their capability.